2014
DOI: 10.1002/ghg.1451
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reservoir modeling at the Illinois Basin – Decatur Project

Abstract: Injecting carbon dioxide (CO2) into the subsurface comes with the added responsibility of understanding the movement of the CO2 once injected, and ensuring that it remains contained in the target reservoir. Consequently, a significant part of the sequestration process is to build and maintain models of the subsurface that will predict the flow of the injected CO2. These models need to integrate all data available so that the subsurface movement of the CO2 can be predicted should changes to the injection parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…[] showed that hysteresis in relative permeability curves was, in fact, important to creating capillary trapping in a reservoir with heterogeneity at the scale of 10 2 −10 3 m. Their simulations were insensitive to hysteresis in capillary pressure curves. A number of other studies have also considered CO 2 sequestration in fluvial reservoirs without representing sedimentary architecture at the scale of our study [e.g., Zhou et al ., ; Delshad et al ., ; Senel et al ., ]. The results of our study indicate that the amount of trapping of CO 2 and the geometry of the CO 2 plume observed may be very different in such simulations if sedimentary architecture is represented at smaller scales and with hysteretic characteristic relationships defined differently for different textural facies.…”
Section: Discussionmentioning
confidence: 99%
“…[] showed that hysteresis in relative permeability curves was, in fact, important to creating capillary trapping in a reservoir with heterogeneity at the scale of 10 2 −10 3 m. Their simulations were insensitive to hysteresis in capillary pressure curves. A number of other studies have also considered CO 2 sequestration in fluvial reservoirs without representing sedimentary architecture at the scale of our study [e.g., Zhou et al ., ; Delshad et al ., ; Senel et al ., ]. The results of our study indicate that the amount of trapping of CO 2 and the geometry of the CO 2 plume observed may be very different in such simulations if sedimentary architecture is represented at smaller scales and with hysteretic characteristic relationships defined differently for different textural facies.…”
Section: Discussionmentioning
confidence: 99%
“…All of the seismic lines and surveys, along with the multiple downhole geophysical investigations for formation properties, were incorporated to produce a series of static and dynamic models including, geologic, velocity and reservoir models (Senel et al, 2014;Will et al, 2016a). Also, inversion of the 3D seismic data along with reservoir properties acquired from well data were used to produce a reservoir flow simulation based on the integrated earth model.…”
Section: Seismic Surveysmentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) FromSenel et al (2014).…”
mentioning
confidence: 99%
“…Upon re-dimensionalization, the equations for wetting and non-wetting fl uid phases become, respectively (19) Subtracting the non-wetting phase fl ow equation from the wetting one, we obtain…”
Section: Gravity-capillary Balancementioning
confidence: 99%
“…who provided a review of the ten years between 2005 and 2015. A recent benchmark of the state‐of‐the‐art is the work by Senel et al . who modeled the Midwest Geologic Sequestration Consortium (MGSC) injection in Illinois .…”
Section: Introductionmentioning
confidence: 99%